Organosilane-Assisted Synthesis of Hierarchical MCM-22 Zeolites for Condensation of Glycerol into Bulky Products - Rodrigues, Mariana V. [UNESP]; Okolie, Chukwuemeka; Sievers, Carsten; Martins, Leandro [UNESP] (American Chemical Society (ACS), 2019)
Hierarchical micro-mesoporous MCM-22 zeolites were synthesized using hexamethyleneimine and organosilanes as structure directing agents, which enabled the formation of hierarchical zeolites with mesopores created by the voids left by the organosilanes after thermal treatment, without loss of the intrinsic microporosity of the zeolite. The addition of organosilanes to the synthesis medium reduced the incorporation of aluminum atoms into the zeolite framework, making the hierarchical zeolites more hydrophobic than the microporous MCM-22 reference material. Measurements of the contact angles between water droplets and the zeolites pressed into wafers confirmed the distinct hydrophobic character of the samples. The zeolites were used as catalysts for the liquid-phase condensation of glycerol with acetone. Diffusion of the bulky products in the purely microporous zeolites was hindered due to steric constraints. On the other hand, the hierarchical zeolites showed improved catalytic performance in the glycerol condensation reaction, due to greater access to the active acid sites and increased hydrophobicity, which helped in removing water formed in the reaction from the zeolite cavities. The zeolite synthesized with the organosilane bearing 12 carbon atoms in the alkyl chain provided glycerol conversion of 83% in 2 h, while limited conversion of 19% was obtained over the purely microporous sample. In addition to the satisfactory catalytic results observed in the glycerol condensation reaction, the one-pot synthesis procedure employed was simple and allowed the creation of hierarchical zeolites with narrow mesopore size ranges and excellent potential for the conversion of platform molecules derived from biomass sources.